Waqf Management Strategy: Efforts to Develop Educational Facilities and Infrastructure at An-Nur Tangkit Islamic Boarding School in Jambi - Husin, Saddam (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to examine waqf management strategies in developing educational facilities and infrastructure at the An-Nur Tangkit Islamic Boarding School, Jambi. As an instrument of Islamic philanthropy, waqf has great potential in supporting the development of educational infrastructure. This study focuses on identifying and analyzing effective waqf asset management strategies to improve the quality of educational facilities in Islamic boarding schools. The research method uses a qualitative approach, with in-depth interviews involving waqf managers, Islamic boarding school administrators and other stakeholders. Field observations and document analysis were also carried out to gain a comprehensive understanding of waqf management practices. The research results show that innovative and sustainable waqf management contributes significantly to the development of educational facilities in Islamic boarding schools. Key strategies identified include diversification of waqf assets, strategic collaboration with the private sector and government, and increasing professionalism in waqf management. This research concludes that optimizing waqf management has a positive impact on the quality of educational infrastructure at the An-Nur Tangkit Islamic Boarding School, Jambi. The recommendations put forward include developing the capacity of waqf managers, utilizing technology for waqf administration, as well as increasing public awareness regarding the importance of waqf as a means of supporting education.